Study on modern malware analysis system - Yi ZHAO; Jian GONG; Wang YANG (Tongxin xuebao)
The analysis of malicious code’s network behavior is an important research field of network security.This function of existed systems is incomplete and not deep.The functions of malicious code are summarized and a comprehensive content is presented.Moreover the network behavior analysis function of existed analysis systems is introduced and CUCKOO which is able to satisfy the requirements of involved study is found.Finally the advantage and points of this application platform were summarized,and an expansion of the system was proposed.